Healing the Exposed Being : The Ngoma healing tradition in South Africa - Thornton, Robert J. (Book collections on Project MUSE., 2017)
This ethnography explores the Ngoma healing tradition as practised in eastern Mpumalanga, South Africa. 'Bungoma' is an active philosophical system and healing practice consisting of multiple strands that is basedon the notion that humans are intrinsically exposed to each other; while this is the cause of illness, it is also the condition for the possibility of healing. This healing seeks to protect the 'exposed being' from harm through augmenting the self. Unlike Western medicine, it does not seek to cure physical ailments but aims to prevent suffering by allowing patients to transform their personal narratives of self. Like Western medicine, it is empirical and is presented as 'local knowledge' that amounts to a practical anthropology of human conflict and the environment. The book examines this anthropology through political, economic, interpretive and environmental lenses and seeks to bring its therapeutic applications into relation with global academic anthropology.